Field notes contributed by David L. Dankert, spring 1996 - Dankert, David L.et al (1996)
Spring report of birds and locations contributed by David L. Dankert. Also included are details of a Greater Scaup sighting. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed